Energy Input-Output Analysis in Rose Oil Agriculture in Isparta Province - Fikret Demir; Osman Gökdoğan (Journal of Agricultural Sciences)
In this study, it was aimed to determine the energy balance in oil rose production in Isparta province in Turkey. Simple random sampling method was used in the selection of enterprises. The survey was applied to 121 the number of farms. In 2008, a preliminary study was done face to face interviews with 121 farms. Rose cultivation trials to determine the energy balance were discussed and the tests were performed in 15 plants. In 15 plants, energy balance sheets were also determinated by observation and measurement methods in 2009 and 2010. Non-parametric data envelopment analysis was used in the measurement of productive activity efficiency. Prediction of productive activity efficiency measurement was made via SPSS and DEAP 2.10 pocket software. In cultivation of rose oil, it was determined that energy input was 16544 MJ ha-1, energy output was 23437.35 MJ ha-1 and output/input ratio 1.42. According the first and second years test results, it was found that the input energy of fertilizer was higher than the human labor energy input. This situation is due to inadequate practices oilseed harvest mechanization especially in the cultivation of roses.